PENGARUH KEBIASAAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA - Sandi Budiana; Nita Karmila; Ratna Devi (FKIP UNIVERSITAS PAKUAN, 2020)
THE EFFECT OF HABIT LEARNING TOWARD MATHEMATICS LEARNING OUTCOMES This research is a quantitative research with a survey approach conducted on fourth grade students of Sukasari State Elementary School, Bogor City, 2020/2021 school years. The populations are 93 student and sample 48 student. The data in this study were obtained throungh an instrument in the for learning habits variables and a test instrument in the form multiple choice questions for variable mathematics learning outcomes. This is based on statistical analysis which produces path coefficients (r_xy) in the amount of 0,335 and the pattern Ŷ = 43,85 + 0,236x. From the level of influence is low and obtained t_count 2,713 greater than t_table1,990 the real level 0,05 significant. Based on the results of the study, it can be concluded that there is a positive influence between the learning habits on the mathematics learning outcomes of fourth grade student.